Kajian Visual Dan Filosofis Waruga Bodas Dalam Konteks Sosio-Kultural Desa Pusakanagara, Baregbeg Ciamis - Setiadi Putra, Edi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2025)
The Waruga Bodas parade is a cultural expression of the people of Pusakanagara Village, Baregbeg District, Ciamis Regency, depicting the spiritual journey of legendary figures from the Galuh Kingdom, such as King Ciung Wanara and King Hariang Banga. This parade not only emphasizes visual beauty but also emphasizes the philosophy of life regarding purity, resilience, and human identity. However, the design of the figures and attributes of Waruga Bodas are not yet fully aligned with the underlying philosophical meaning. This study aims to examine the relationship between the visual form and philosophical meaning of Waruga Bodas through a Sundanese aesthetic approach and the socio-historical context of the Galuh community. The methods used include visual analysis of visual elements and symbolism based on social media documentation and local publications. The results demonstrate the importance of updating the design to better reflect Sundanese philosophical values ​​and aesthetics that are contextual to the culture of Pusakanagara Village.